Reinforcing Skeletal System lesson using cycle of internalized learning in English class - Shukor, Farhana (Universiti Teknologi MARA, Cawangan Melaka., 2019)
This study is aimed to investigate the readiness of 53 first semester diploma students in learning Skeletal System lesson in English class using five stages of Cycle of Internalized Learning. They learned in Health Science lecture about Skeletal System and being revised about the same topic in English class. In the following week, they were assigned with the task to illustrate individually the anatomical diagram of long bones, discuss about the article given and solve critical thinking question from their presentation. Opinions from the students were sought after to get their feedback on the three best things about the lesson and three things they would most likely to see improved. Semi-structured interview sessions were conducted to elicit responses from the students. It is then viewed to be the responsibility of the curriculum designer as well as the language instructor to plan and implement more lessons that will promote cooperative learning among these students. The students needed support from the lecturers to be able to complete the task assigned successfully and in the long run can apply the skills learned at their future workplace.